2011
DOI: 10.2355/isijinternational.51.115
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Sag Line Formation on the Zinc-coated Steel Strip after the Gas-jet Wiping in the Continuous Hot-dip Galvanizing Process

Abstract: of the coating thickness for long wavelength perturbations. Ellen and Tu 3) have suggested a non-dimensional model that takes into account the surface shear stress and their model gives significantly more accurate prediction of the final coating thickness. Also, Tu and Wood 4) have experimentally demonstrated that the final coating thickness depends on both the pressure and shear stress distributions on the strip surface. Although Tuck and Vanden-Broeck.5) and Yoneda 6) suggested that the final thickness dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(36 reference statements)
0
8
0
1
Order By: Relevance
“…The mean coating thickness distribution along the longitudinal y-direction is computed by using the method of Ellen and Tu, 3) hereinafter called "Ellen and Tu's model". And in order to compute the coating thickness distribution along the transverse z-direction quickly, the mathematical perturbation method proposed in our recent paper 4) is used. Also, the relaxation time that was suggested in that paper is used to determine the longitudinal position where the thickness of the coated layer is settled.…”
Section: Numerical Simulations Of Check-mark Stainmentioning
confidence: 99%
“…The mean coating thickness distribution along the longitudinal y-direction is computed by using the method of Ellen and Tu, 3) hereinafter called "Ellen and Tu's model". And in order to compute the coating thickness distribution along the transverse z-direction quickly, the mathematical perturbation method proposed in our recent paper 4) is used. Also, the relaxation time that was suggested in that paper is used to determine the longitudinal position where the thickness of the coated layer is settled.…”
Section: Numerical Simulations Of Check-mark Stainmentioning
confidence: 99%
“…Additionally, they are used to provide humidity to foods in the food sector [1][2][3]. Air knives are commonly used in the continuous hot dip galvanizing procedure, a coating technique in the steel industry [4][5][6][7][8][9][10][11]. The paper industry is one with effective use of air knives in the thermal paper production process where a very thin layer of chemicals is spread on paper [12].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers made a variety of recommendations to prevent errors and control the coating thickness for zinc-coated surfaces in continuous hot dip galvanizing processes [4,6,8,10]. So et al [4], analyzed surface flaws (which called sag lines) on steel sheet surfaces and developed a new model to predict the variation in coating thickness. They performed 3-D CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It is envisaged that fluctuation of this wall pressure and wall shear stress cause variation in coating thickness. Recent studies [6][7][8][9][10] have shown the ripples on the coating surface are correlated to the fluctuating impinging pressure and shear stress which in turn is a consequence of the jet oscillation. Numerical studies of air-coating liquid interaction showed that jet oscillation is reflected on the final coating thickness 9,10) with the low frequency components of the impingement wall pressure fluctuation correlated to the waviness of the coating surface.…”
Section: Introductionmentioning
confidence: 99%